Sevoflurane Induces Coherent Slow-Delta Oscillations in Rats - Guidera, Jennifer A.; Taylor, Norman E.; Lee, Justin T.; Vlasov, Ksenia Y.; Pei, JunZhu; Stephen, Emily P.; Mayo, J. Patrick; Brown, Emery N.; Solt, Ken (Frontiers in Neural Circuits, 2017)
Sevoflurane is an inhalational anesthetic routinely administered to surgical patients to induce unconscious. Sevoflurane induces characteristic oscillations in the electroencephalogram (EEG) that are useful for monitoring the brain state of surgical patients. However, it is not known how sevoflurane-induced oscillations are generated within the brain, or how they relate to unconsciousness. The rat is a potential animal model for studying sevoflurane-induced oscillations within the brain, but whether sevoflurane induces similar surface-level oscillations in rats and humans is not known. In rats, we characterized changes in the extradural EEG and intracranial local field potentials (LFPs) within the prefrontal cortex (PFC), parietal cortex (PC) and central thalamus (CT) in response to progressively higher doses of the inhaled anesthetic sevoflurane. During induction with a low dose of sevoflurane, beta/low gamma (15 – 40 Hz) power increased in the frontal EEG and PFC, PC and CT LFPs, and PFC-CT and PFC-PFC LFP beta/low gamma coherence increased. Loss of movement coincided with an abrupt decrease in beta/low gamma PFC-CT LFP coherence. Following loss of movement, cortically coherent slow-delta (0.1 – 4 Hz) oscillations appeared. At higher doses of sevoflurane sufficient to induce loss of the righting reflex, coherent slow-delta oscillations dominated. Dynamics similar to those observed during induction were observed as animals emerged and recovered from sevoflurane anesthesia. We conclude that sevoflurane induces similar surface-level EEG dynamics in rats and humans, and that coherent slow-delta oscillations are a correlate of sevoflurane-induced decreased arousal in rats.